Chip-delay locked matched filter for DS-CDMA systems using long sequence spreading. - Yoon, Y.C (IEEE Transactions on communications)
This paper considers an improved single-user detection technique for asynchronous direct-sequence code-division multiple-access (DS-CDMA) systems using long sequence spreading (random-CDMA) Most of the known detection schemes for DS-CDMA suffer from either poor performance under power-imbalance (near-far like) conditions, excessive complexity, or incompatibility with systems employing long sequence spreading. To address these problems, this paper considers a signal-to-noise ratio maximizing linear time-invariant filter for one-shot bit symbol detection exploiting some information about the interferers. This filter, referred to as the chip-delay locked matched filter (CLMF), exploits the cyclostationarity in multiple-access interference, and it can offer good near-far resistance while remaining suitable for systems with long sequence spreading. The CLMF requires knowledge of interferers chip delays and signal powers; however, knowledge of their pseudonoise sequences is unnecessary. This paper also demonstrates the improvement in performances offered by the CLMF over other single-user receivers such as the conventional matched filter and noise-whitening matched filter performance is evaluated in terms of probability of outage for single-rate and dual-rate DS-CDMA systems using bandwidth-efficient chip pulses, over a single-path additive white Gaussian noise channel. Errors in the interferer chip delay estimates degrade the CLMF performance. However, if the root-mean-square value of these errors is less than 5% of the chip interval, then this degradation is small